Hypolipidemic and insulin sensitizing effects of salsalate beyond suppressing inflammation in a prediabetic rat model - Hüttl, Martina; Markova, Irena; Miklánková, Denisa; Zapletalova, Iveta; Kujal, Petr; Šilhavý, Jan; Pravenec, Michal; Malinska, Hana (Frontiers in Pharmacology, 2023)
Background and aims: Low-grade chronic inflammation plays an important role in the pathogenesis of metabolic syndrome, type 2 diabetes and their complications. In this study, we investigated the effects of salsalate, a non-steroidal anti-inflammatory drug, on metabolic disturbances in an animal model of prediabetes - a strain of non-obese hereditary hypertriglyceridemic (HHTg) rats. Materials and Methods: Adult male HHTg and Wistar control rats were fed a standard diet without or with salsalate delivering a daily dose of 200 mg/kg of body weight for 6 weeks. Tissue sensitivity to insulin action was measured ex vivo according to basal and insulin-stimulated 14C-U-glucose incorporation into muscle glycogen or adipose tissue lipids. The concentration of methylglyoxal and glutathione was determined using the HPLC-method. Gene expression was measured by quantitative RT-PCR. Results: Salsalate treatment of HHTg rats when compared to their untreated controls was associated with significant amelioration of inflammation, dyslipidemia and insulin resistance. Specificaly, salsalate treatment was associated with reduced inflammation, oxidative and dicarbonyl stress when inflammatory markers, lipoperoxidation products and methylglyoxal levels were significantly decreased in serum and tissues. In addition, salsalate ameliorated glucose tolerance and reduced serum lipid concentrations. Insulin sensitivity in visceral adipose tissue and skeletal muscle was significantly increased after salsalate administration. Further, salsalate markedly reduced hepatic lipid accumulation (triglycerides -29% and cholesterol -14%). Hypolipidemic effects of salsalate were associated with differential expression of genes coding for enzymes and transcription factors involved in lipid synthesis (Fas, Hmgcr), oxidation (Ppar) and transport (Ldlr, Abc transporters), as well as changes in gene expression of cytochrome P450 proteins, in particular decreased Cyp7a and increased Cyp4a isoforms. Conclusions: These results demonstrate important anti-inflammatory and anti-oxidative effects of salsalate that were associated with reduced dyslipidemia and insulin resistance in HHTg rats. Hypolipidemic effects of salsalate were associated with differential expression of genes regulating lipid metabolism in the liver. These results suggest potential beneficial use of salsalate in prediabetic patients with NAFLD symptoms.